Lotus tenuis seedlings subjected to drought or waterlogging in a saline sodic soil - García, Ileana Vanesa (2014)
The growth response of Lotus tenuis seedlings to drought and waterlogging in a saline-sodic soil, themobilization of Na+ in tissue, and the association with native AM fungi and Rhizobium bacteria werestudied by means of two experiments under controlled conditions.In the first experiment, we tested the effect of the duration of waterlogging on seedlings very early aftersowing, when they had the two cotyledons totally expanded and, in the second experiment, we tested theeffect of water stress on seedlings of different growth stages, at a wide range of water availability in thesoil, from deficit to water excess L. tenuis seedlings were able to deal with the intensity of water stress atvery early growth stages. They established symbiotic associations with AM fungi and Rhizobium bacteriaand regulated Na+ concentration in plant tissue to prevent leaf injury. The seedling strategy consistedin decreasing the shoot:root ratio under water deficit and increasing the shoot:root ratio under waterexcess.Lotus seedlings are highly tolerant to the combination of water and salt stress from early stages in theirdevelopment and early plant establishment in adverse soil conditions is an important ability of L. tenuisseedlings to grow and survive longer within a grassland ecosystem.